Leveraging Phonetic and Speech Research for Irish Language Revitalisation and Maintenance - Ni Chiarain, Neasa; Gobl, Christer; Ni Chasaide, Ailbhe; Barnes, Emily (My University, 2019)
The ABAIR initiative illustrates how phonetic research can drive innovative applications that provide endangered-language communities with powerful tools and resources for language maintenance and revitalisation. ABAIR encompasses a cluster of Irish-language projects with parallel basic and applied research strands. These reflect its evolution from (i) developing phonetic/speech resources to (ii) building technologies (to date, TTS) that use these resources, and to (iii) implementing applications that exploit both resources and technologies to meet urgent needs of the language communities. A key feature is the ongoing collaboration with the language communi¬ties. Rather than passive recipients of resources (developed for commercial purposes), they actively help in setting research priorities, assisting the design, testing and dissemination of outputs, and increasingly, in the collection/curation of data. The paper describes two specific areas, education and access – both pillars of language maintenance – where phonetic resources and applications are impacting.
ICPhS 2019: the 19th International Congress of Phonetic Sciences
PUBLISHED
Melbourne, Australia
Keywords: Irish; Phonetic resources; Speech technology; Digital Humanities; Making Ireland; Educational applications of Speech Technology; Irish Linguistics; Speech and Language Technology; Speech and Language Technology in Education; Speech technology